PERTIMBANGAN HAKIM DALAM MENJATUHKAN PIDANA TERHADAP PELAKU PENCABULAN ANAK YANG MENDERITA DISABILITAS INTELEKTUAL (STUDI PUTUSAN NOMOR 135/PID.SUS/2018/PN BTG): The Judge's Considerations In Sentenced Criminal Against Child Abuse Offenders Suffering From Intellectual Disabilities - Owen Chinua Saragih; Ermania Widjajanti (Faculty of Law, Universitas Trisakti, 2024)
The crime of child molestation can be committed by anyone, in this case the perpetrator of child molestation has an intellectual disability. The formulation of the problem this research is whether the judge's consideration in imposing a 5 year prison sentence on the perpetrator of the crime of obscene acts on a child who has a mental disorder is correct and what is the strength of the evidence from expert testimony on the perpetrator of the crime of an obscene act on a child who has a mental disorder. The research method is descriptive analytical with secondary data analyzed qualitatively, type of research is normative juridical. The results of the research and discussion show that the judge's considerations in this case imposed a criminal sentence of 5 (five) years on the perpetrator because the judge assumed that the perpetrator could be responsible for his actions, even though the perpetrator as in this case was mentally retarded, he was still sentenced because he was declared capable of responsibility. Conclucion case could be returned to the law regarding legal competence, eliminating the basic crime because forgiveness could given if the fraudster is unable to take responsibility (Article 44 of the Criminal Code).